Exploring ordinary theology : everyday Christian believing and the church - Astley, Jeff; Francis, Leslie J. (Explorations in practical, pastoral, and empirical theology., 2013)
Ordinary theology' characterizes the reflective God-talk of the great majority of churchgoers, and others who remain largely untouched by the assumptions, concepts and arguments that academic theology takes for granted. Astley coined the phrase in his innovative study, Ordinary Theology: Looking, Listening and Learning in Theology, arguing that 'speaking statistically ordinary theology is the theology of God's Church'. Exploring Ordinary Theology presents fresh contributions from a wide range of authors, who address the theological, empirical and practical dimensions of this central feature of.